An altered heparan sulfate structure in the articular cartilage protects against osteoarthritis. Issue 7 (July 2020) - Severmann, A.-C.; Jochmann, K.; Feller, K.; Bachvarova, V.; Piombo, V.; Stange, R.; Holzer, T.; Brachvogel, B.; Esko, J.; Pap, T.; Hoffmann, D.; Vortkamp, A.
Summary: Objective: Osteoarthritis (OA) is a progressive degenerative disease of the articular cartilage caused by an unbalanced activity of proteases, cytokines and other secreted proteins. Since heparan sulfate (HS) determines the activity of many extracellular factors, we investigated its role in OA progression. Methods: To analyze the role of the HS level, OA was induced by anterior cruciate ligament transection (ACLT) in transgenic mice carrying a loss-of-function allele of Ext1 in clones of chondrocytes ( Col2-rtTA-Cre;Ext1 e2fl/e2fl ) . To study the impact of the HS sulfation pattern, OA was surgically induced in mice with a heterozygous ( Ndst1 +/− ) or chondrocyte-specific ( Col2-Cre;Ndst1 fl/fl ) loss-of-function allele of the sulfotransferase Ndst1. OA progression was evaluated using the OARSI scoring system. To investigate expression and activity of cartilage degrading proteases, femoral head explants of Ndst1 +/− mutants were analyzed by qRT-PCR, Western Blot and gelatin zymography. Results: All investigated mouse strains showed reduced OA scores ( Col2-rtTA-Cre;Ext1 e2fl/e2fl : 0.83; 95% HDI 0.72–0.96; Ndst1 +/− : 0.83, 95% HDI 0.74–0.9 ; Col2-Cre;Ndst1 fl/fl : 0.87, 95% HDI 0.76–1). Using cartilage explant cultures of Ndst1 animals, we detected higher amounts of aggrecan degradation products in wildtype samples (NITEGE 4.24-fold, 95% HDI 1.05–18.55; VDIPEN 1.54-fold, 95% HDI 1.54–2.34). Accordingly, gelatin zymography revealed lower Mmp2 activity in mutant samples upon RA-treatment (0.77-fold, 95% HDI: 0.60–0.96). As expression of major proteases and their inhibitors was not altered, HS seems to regulate cartilage degeneration by affecting protease activity. Conclusion: A decreased HS content or a reduced sulfation level protect against OA progression by regulating protease activity rather than expression.